N. F. S. Grundtvigs bopæle (adresser) i København - Johansen, Steen (Grundtvig-Studier, 1960)
Places at which N. F. S. Grundtvig stayed in Copenhagen. Up to 1821. By Steen Johansen. The essay consists exclusively of some biographical observations concerning N. F. S. Grundtvig, inasmuch as it attempts to give an exact account of the places at which Grundtvig stayed in Copenhagen from the year 1800, when he entered the University, until his death 1872. However, the section which is printed here deals only with the period from 1800 to 1821, since the period from 1821 to 1872 must await further research. By way of introduction there are some observations on the places at which Grundtvig is presumed to have stayed when he was a pupil at the Latin School in Aarhus. There is a thorough discussion of the question as to where in Copenhagen Grundtvig lived during his time as a student ( 1800- 03). In addition, special attention is paid to the period from 181 1 to 1821, which incidentally is still one of the most obscure periods of Grundtvig’s life from the biographical points of view. Here an attempt is made to give the correct sequence of Grundtvig’s addresses during the period. Finally, some remarks about the possible significance of this investigation for an understanding of Grundtvig. His unsettled life as a student, when he lived sometimes in Copenhagen, sometimes at home in South Sjaelland or in other places, undoubtedly reflects his inner life, which at that time was still immature and lacking in concentration. But later—and here one thinks especially of the years from 18 1 1 to 1821, which were full of ferment and very productive— Grundtvig’s frequent changes of residence must certainly be an expression of utter indifference as to where and how he lived. During these years he was very dependent on his family (his own and his future wife’s), and on his uncertain earnings as a writer, for his housing accommodation. Only when he was 37 years of age did he obtain his first “position” from a citizen’s point of view.